Trends in initiation of direct oral anticoagulant therapies for atrial fibrillation in a national population-based cross-sectional study in the French health insurance databases. Issue 3 (30th March 2018) - Huiart, Laetitia; Ferdynus, Cyril; Renoux, Christel; Beaugrand, Amélie; Lafarge, Sophie; Bruneau, Léa; Suissa, Samy; Maillard, Olivier; Ranouil, Xavier
Abstract : Objective: Unlike several other national health agencies, French health authorities recommended that the newer direct oral anticoagulant (DOAC) agents only be prescribed as second choice for the treatment of newly diagnosed non-valvular atrial fibrillation (NVAF), with vitamin K antagonists (VKA) remaining the first choice. We investigated the patterns of use of DOACs versus VKA in the treatment of NVAF in France over the first 5 years of DOAC availability. We also identified the changes in patient characteristics of those who initiated DOAC treatment over this time period. Methods: Based on the French National Health Administrative Database, we constituted a population-based cohort of all patients who were newly treated for NVAF between January 2011 and December 2015. Trends in drug use were described as the percentage of patients initiating each drug at the time of treatment initiation. A multivariate analysis using logistic regression model was performed to identify independent sociodemographic and clinical predictors of initial anticoagulant choice. Results: The cohort comprised 814 446 patients who had received a new anticoagulant treatment for NVAF. The proportion of patients using DOACs as initial anticoagulant therapy reached 54% 3 months after the Health Ministry approved the reimbursement of dabigatran for NVAF, and 61% by the end of 2015, versus VKA use. In the multivariate analysis, we found that DOAC initiators were younger and healthier overall than VKA initiators, and this tendency was reinforced over the 2011–2014 period. DOACs were more frequently prescribed by cardiologists in 2012 and after (adjusted OR in 2012: 2.47; 95% CI 2.40 to 2.54). Conclusion: Despite recommendations from health authorities, DOACs have been rapidly and massively adopted as initial therapy for NVAF in France. Observational studies should account for the fact that patients selected to initiate DOAC treatment are healthier overall, as failure to do so may bias the risk–benefit assessment of DOACs.